The 21st Century Students Stress Reliever a Study of Student Perceptions: Gandharva Veda Music - Aricksuy, I Dewa Ayu Istri; Marselinawati, Putu Sri (Institute for Advanced Science, Social, and Sustainable Future, 2023)
Maharishi Ayur-Veda is a centuries-old authentic health care scheme, brought to light by Maharishi Mahes Yogi based on the ancient Vedic tradition, additionally it is a completely holistic healthcare system. In this study paper we will learn and know more about what is Gandharva Veda Music, and how it help to reduce the students stress level, and how it is generally impact. This research are conducted to know how is students perceptions in using Gandharva Veda music as a study music or sleeping music as stress reliever. Which lead to a questions, “How students feels about Gandharva Vedic Music as a stress reliever”. By that, some questionnaire will share and there will be some questions that will show how they feels and how it helps them in releasing stress. The sampling that chosen is Quota sampling. The population of this research are 10 students from High school to University, from the age of 16years above which known that they are facing examinations (for 12th grade class of high school) and studying while working university students. The data tools collection used is questionnaire which shared by social media. There was 11 questions which are shows Anxiety/Stress level (questions number 1-6) and how they think about the Gandharva Vedic Music ( questions number 7-11). This questionnaire will be share to 10 people who are students. This research shows that 70% from the subject feels anxious, and 70% of the subject are unsure that they are performed well in class. also it is shows that Gandharva Veda music at least helps to reduce the subject stress levels, feel relax with the help of Gandharva Vedic music and shows that Gandharva Veda music at least helps to reduce the subject stress levels It is known that these day students get anxious and stress easily, with a lot of caused. However they are still force their self to deal with the situations with exhausted feeling. Gandharva Vedic music which known as the music therapy giving the vibration of happiness and help them to reduce their stress level. In the need of this aspect of stress and anxiety disorder this kind of research should be expand in the future and hopefully it could help not only them but all students all over the world